Pengaruh Konvergensi IFRS dan Kompleksitas Operasi Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Pada Perusahaan Food and Beverage di Indonesia - Khayati, Isnaini Nur; Achyani, Fatchan (Economics and Digital Business Review, 2024)
The aim of this research is to determine and analyze the influence of IFRS convergence, operational complexity, institutional ownership and public ownership on the timeliness of submitting financial reports. The population of this research is food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2021 period. In this research, the data used is secondary data with a sampling technique carried out using the purposive sampling method. The number of samples used was 128 companies. The research results provide empirical evidence that operational complexity and public ownership influence the timeliness of submitting financial reports. Meanwhile, IFRS convergence and institutional ownership have no effect on the timeliness of submitting financial reports.